2020
DOI: 10.3727/096504019x15615433287579
|View full text |Cite
|
Sign up to set email alerts
|

miR-122 Inhibits Hepatocarcinoma Cell Progression by Targeting LMNB2

Abstract: In the present study, we investigated the role of miR-122 in hepatocarcinoma progression and explored the mechanism. In hepatocarcinoma tissues and cells, we used qRT-PCR to validate the miR-122 expression level. Next, we used colony formation by crystal violet staining assay to compare cell proliferation ability, and we used scratch test or Transwell assay to compare cell migration or invasion ability. We then conducted bioinformatics or luciferase reporter gene assay to prove the regulation effect of miR-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…LMNB2 is a nuclear lamin protein and may be one of the intra-nuclear targets [12]. It was reported that microRNA-122 inhibits HCC cell progression via targeting LMNB2 [26]. LMNB2 was also found to be significantly related with NSCLC progression [22].…”
Section: Discussionmentioning
confidence: 99%
“…LMNB2 is a nuclear lamin protein and may be one of the intra-nuclear targets [12]. It was reported that microRNA-122 inhibits HCC cell progression via targeting LMNB2 [26]. LMNB2 was also found to be significantly related with NSCLC progression [22].…”
Section: Discussionmentioning
confidence: 99%
“…7 An in vitro study was conducted, which identified LMNB2 as a novel downstream target of miR-122 in promoting liver cancer. 13 However, the role of LMNB2 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that increased lamin B2 expression was associated with advanced clinicopathological characteristics of NSCLC, and that lamin B2 enhanced NSCLC occurrence and progression by interacting with the minichromosome maintenance complex component 7 7 . An in vitro study was conducted, which identified LMNB2 as a novel downstream target of miR‐122 in promoting liver cancer 13 . However, the role of LMNB2 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the tumor suppressor contained in the exosomes can directly exhibit tumor suppression effects. For example, studies have shown that exosomal miR-122 produced by hepatocellular carcinoma can inhibit EMT, increase drug sensitivity, and inhibit angiogenesis by targeting LMNB2 [83,84]. On the other hand, because exosomes are lipid-like and easy to metastasize, their stable membrane structure is certainly an advantage for the stability of such vehicles following intravenous injection.…”
Section: Exosomes Are Therapeutic Targets Of Hccmentioning
confidence: 99%